PENYELESAIAN SENGKETA KONSUMEN PADA BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) KOTA BANDUNG - Arimba, Cahya Iradi; Mutakin, Dede (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
Consumer protection issues have become a frequent topic of discussion in society today. Many consumers feel disadvantaged by the actions of business actors, making consumer protection an important issue. Often, consumers' rights are neglected by business actors, leaving a sense of dissatisfaction among consumers. According to the law, consumers have the right to file complaints with the Consumer Dispute Settlement Body (BPSK). This research uses a normative legal approach with descriptive analysis based on data collection. A qualitative research method is applied through inductive analysis to gather and explore various relevant facts. The establishment of the Consumer Dispute Settlement Body (BPSK) aims to provide effective protection for both consumers and business actors by designing a protection system that guarantees legal certainty and transparency. In the city of Bandung, the Consumer Dispute Settlement Body (BPSK) has four stages of dispute resolution, starting with Registration of Complaints, Pre-Trial, Trial, and Verdict.